1 Introduction and overview. (November 2022) - Galanakis, Yannis; Parikh, Tulsi
Abstract : This introduction presents the structure and contents of the current issue of Archaeology in Greece . It also offers an overview (not meant to be exhaustive) of archaeological activity in Greece over the past 12 months, focusing on major exhibitions and other cultural events as well as on important recent publications.